Perioperative intravenous corticosteroids reduce incidence of atrial fibrillation following cardiac surgery: a randomized study - Abbaszadeh,Monir (2012)
OBJECTIVE: Corticosteroids decrease side effects after noncardiac elective surgery. A randomized, double blinded, placebo-controlled study was plan to test the hypothesis that standard doses of dexamethasone (6X2) would decrease the incidence of atrial fibrillation (AF) following cardiac surgery. METHODS: A total of 185 patients undergoing coronary revascularization surgery were enrolled in this clinical study. The anesthetic management was standardized in all patients. Dexamethasone (6 mg/ml) or saline (1 ml) was administered after the induction of anesthesia and a second dose of the same study drug was given on the morning after surgery. The incidence of AF was determined by analyzing the first 72 hours of continuously recorded electrocardiogram records after cardiac surgery, to determine the incidence and severity of postoperative side effects. RESULTS: The incidence of 48 hours postoperative AF was significantly lower in the Dexamethasone group (21/ 92[37.5%]) than in the placebo group (35/92 [62.5%], adjusted hazard ratio, 2.07; 95% confidence interval, 1.09-3.95 (P<0.05). Compared with placebo, patients receiving dexamethasone did not have higher rates of superficial or deep wound infections, or other major complications. CONCLUSIONS: Prophylactic short-term dexamethasone administration in patients undergoing coronary artery bypasses grafting significantly reduced postoperative atrial fibrillation.